EFFECT OF PHYSICAL ACTIVITY AND FAST FOOD CONSUMPTION FREQUENCY ON OVERWEIGHT LEVEL AMONG HIGH SCHOOL ADOLESCENT - Harlianti, Lita; Pratiwi, Witri; Nauphar, Donny; Suhaeni, Eni (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2018)
Background: Obesity was believed to be one of the risk factors of degenerative diseases, such as diabetes mellitus, hypertension, and coronary heart disease. Obesity occurred gradually that started with overweight. Risk factors for overweight are lack of physical activity, and consumption of high caloric fatty food which may cause accumulation of fats inside the body. This research aims to examine the effect of physical activity and fast food consumption frequency on overweight level among high school adolescent in Cirebon. Methods: It was a cross-sectional study conducted among 262 high school students aged 15-17 years using stratified random sampling. Results: The result based on Spearman correlation test showed negative correlation between physical activity and overweight level with p= 0,001 (p< 0,05) and correlation coefficient of -0,627. There was positive correlation between consumption fast food frequency with overweight with p=0,037 (p=0,05) and correlation coefficient of 0,423. Conclusions: Physical activity and fast food consumption frequency have effects on overweight level in high school adolescent in Cirebon.